Changing Language Skills and Trade in Europe - Michael Rindler (ZBW - Leibniz Information Centre for Economics, 2021)
I investigate the effect of changing language skills on trade using an unique panel data set on spoken language. It tracks over thirty, mostly European, countries from the mid-90s to the beginning of the 2010s. In this period, European countries have witnessed an advancing trade integration and large changes in foreign language knowledge. I estimate a significant and positive effect of changing common English skills on trade using the gravity model and controlling for endogeneity by pair fixed effects and a globalization trend. General equilibrium welfare analysis shows that all countries except for Russia profited from the rise in the percentage of English speakers. Further, in a re-estimation of Fidrmuc and Fidrmuc (2016), I find a significant causal impact of aggregate common spoken language on trade, but not for any specific language.
Keywords: F14; F15; Z13; 330; language; international trade; gravity model